PENGARUH RETURN ON ASSETS (ROA) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM (STUDI KASUS PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019–2023) - Raharja, Fariz Dharmawan; Rahmat, Kamaluddin; Anggraeni, Windi Ariesti (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2024)
This study aims to determine the effect of partial and simultaneous Variable Return on Assets (ROA) and Debt to Equity Ratio (DER) on Stock Prices in Property and Real Estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The population in this study is property and real estate sector companies listed on the Indonesia Stock Exchange in 2019-2023. Sample selection was done using purposive sampling technique, so that 13 companies were sampled in this study. The research methods used are quantitative methods with descriptive verification analysis, classical assumption test, hypothesis test with multiple linear regression analysis. The Data is processed using IBM SPSS 26 Software program. The results of this study showed that Return on Assets affect Stock Prices, Debt to Equity Ratio affect Stock Prices, Return on Assets and Debt to Equity Ratio simultaneously affect Stock Prices.Keywords: Debt to Equity Ratio; Return on Assets; Stock Prices